Effect of arbuscular mycorrhizal fungi on growth of two genotypes of Malpighia emarginata D.C. - Costa, Cynthia Maria Caneiro; Maia, Leonor Costa; Cavalcante, Uided Maaze Tuburcio; Nogueira, Rejane Jurema Mansur Custódio (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this research was to evaluate the effect of inoculation with arbuscular mycorrhizal fungi (AMF) on growth of seedlings of Malpighia emarginata D.C. Stakes of these two genotypes (Barbados and Miró), with two pairs of leaves, were planted for rooting of the seedlings. After two months, a greenhouse experiment was performed, inoculating two AMF species (Gigaspora margarita Becker & Hall and Glomus etunicatum Backer & Gerdemann) under the seedlings, in soils with 3 mg/dm3 phosphorus. At the end of the experiment (110 days), it was observed that the inoculation with AMF enhanced height, shoot dry mass, leaf area, and presented positive correlations among some plant growth characters and among those and number of AMF spores, in comparison with the uninoculated controls. The inoculation with G. margarita produced higher growth responses for both genotypes. The P concentration on the shoots did not vary among treatments. The symbiosis with AMF reduced at least in two months the time for seedlings production on both genotypes of Malpighia emarginata.